Everyday Religiosity and the Politics of Belonging in Ukraine - Wanner, Catherine, 1960- (Book collections on Project MUSE., 2022)
"The Maidan protests of 2013-14 and the outbreak of a hybrid war in Eastern Ukraine in 2014 have led to an expansion of informal religious practices in public institutions, public space, and politics in Ukraine"--